Uncertain Values : An Axiomatic Approach to Axiological Uncertainty - Riedener, Stefan (Berlin/Boston De Gruyter, 2021)
How should you evaluate your options if you re uncertain about what s fundamentally valuable? This book introduces an axiomatic approach to explicate and vindicate Expected Value Maximisation. The result is a formally cogent and philosophically compelling extension of standard decision theory and an original take on the problem of axiological or normative uncertainty.
Schweizerischer Nationalfonds zur Förderung der Wissenschaftlichen Forschung
English
Keywords: History of Western philosophy; Western philosophy: c 1600 to c 1900; Western philosophy, from c 1900 -; Ethics & moral philosophy; Normative uncertainty; intertheoretic comparisons; expected value; representation theorems